Hydrogen sulfide signaling in plant response to temperature stress - Li, Zhong-Guang; Fang, Jue-Rui; Bai, Su-Jie (Frontiers in Plant Science, 2024)
In the past 300 years, hydrogen sulfide (H 2 S) has always been deemed as a toxic gas.Nowadays, it has been found to be a novel signaling molecule in plants, which participates in the regulation of cellular metabolism, seed germination, plant growth, development, and response to environmental stresses, including high temperature (HT) and low temperature (LT). H 2 S, as a signaling molecule, can be actively synthesized and degraded in the cytosol, chloroplasts, and mitochondria of plant cells by enzymatic and non-enzymatic pathways to maintain homeostasis. Till now, the receptors of H 2 S have not been found in plants. It usually exerts physiological functions by persulfidation of target proteins. In the past 10 years, H 2 S signaling in plants has gained much attention. Therefore, in this review, using the attention as a base, H 2 S homeostasis, protein persulfidation, and the signaling role of H 2 S in plant response to HT and LT stress were summarized. Also, the common mechanisms of H 2 S-induced plant HT and LT tolerance were updated. The mechanisms are involved in rebuilding of biomembrane integrity, synthesis of stress proteins, reinforcement of antioxidant system and methylglyoxal (MG) detoxification system, augmentation of water homeostasis system, and reestablishment of Ca 2+ homeostasis and acid-base balance. These updates lay the foundation for further understanding the physiological functions of H 2 S and acquiring temperature stress-resilient crops to develop sustainable food and agriculture.